ダイ18ジ ナンキョク チイキ カンソクタイ カイヨウ ブモン ホウコク - 小田, 勝之; オダ, カツユキ; 今西, 孚士; イマニシ, タカノリ; ODA, Katsuyuki; IMANISHI, Takanori (国立極地研究所, 1979)
P(論文) 第18次南極地域観測において,定常観測(1976-1977)として海上保安庁水路部の担当した海洋観測の結果を報告する. This report presents the results of oceanographic observations, which were carried out by the 18th Japanese Antarctic Research Expedition in 1976-1977. departmental bulletin paper